Agent-supported negotiations in the e-marketplace. (3rd March 2005) - Chen, Eva; Vahidov, Rustam; Kersten, Gregory E.
A key requirement for customer-oriented e-marketplaces is the personalisation and customisation of products and services, as well as personalised fulfilment. Negotiations are at the core of these processes. In this paper an e-marketplace, eAgora, is discussed. It allows buyers and sellers to engage in multi-issue negotiations. eAgora implements several protocols based on a negotiation phase model constructed for this system. Its services include a software agent that generates and critiques offers. Based on a small-scale usability testing with participants, who conducted negotiations with and without the agent, the agent's services were found useful. The users also requested additional agent's services including enhanced offer critique and partial negotiation automation.